Accounting Theory and Practice, Advanced (Book). - Simon, Sidney I. (The Accounting Review, 1962)
Reviews the book "Accounting Theory and Practice, Advanced," by Robert R. Milroy, Robert E. Walden and L. Vann Seawell.